Growth, Wages and Unemployment - The Economic Impact of Refugee Migration on Europe: A Synthetic Control Analysis - Can Karaarslan (Hochschule Offenburg, Fakultät Medien, 2020)
During the year 2015 almost 1.4 million refugees arrived in Europe (eurostat, 2020). Germany was with 1.1 million individuals the major destination (Statista, 2018). A huge political divide occurred over this influx. While welcoming scenes dominated the media in the advent of the so called 'refugee crisis', criticism over the 'We'll-make-it policy' by Angela Merkel increased also among Christian Democrats.1A sudden human influx of such size into a society might not only have political, cultural and social impacts, but may also lead to economic disruptions. Human beings embody consumers as well as labour force. A significant increase in population might thus cause an increase in demand for commodities and in labour supply, which ceteris paribus simultaneously lead to increasing GDP and decreasing wages. Previous literature utilized quasi-natural experiments which can be exploited in social sciences for the detection of causal relations and the usage of methods, not applicable otherwise. The present paper applies the synthetic control methodology to wages, unemployment and economic growth in Germany in order to measure the causal impact of the 2015- refugee influx on these economic key elements. No impact on either of the economic factors has been found. European Union labour market and welfare policies are concerned with the protection of European citizens from disruptive processes. Falling wages and increasing unemployment, as well as decreasing production and consumption embody highly disruptive political potential. Thus, the findings concerning the impact of refugee migration into the European Union might influence EU-policies in the prospect of increased migration to Europe in the upcoming century due climate change and new crises. The remainder of the article is organized as follows: The lessons from the key literature concerning quasi- natural experiments and the impact of migration on wages, unemployment and economic growth are provided in section 2. Section 3 comprises the theoretical framework concerning the differences between refugees and economic migrants. Section 4 introduces the estimation strategy, while section 5 presents data and descriptive statistics. Section 6 shows the simulation results, followed by the concluding discussion in section 7.
urn:nbn:de:bsz:ofb1-opus4-49926
Keywords: 330; Economic Impact; Refugee Migration